Effect of long‐term exposure and delayed drying time on moisture and mechanical integrity of flooded homes. Issue 3 (16th September 2013) - Aglan, H.; Ludwick, A.; Kitchens, S.; Amburgey, T.; Diehl, S.; Borazjani, H.
Abstract A housing flood unit (FU) and large wall section samples were constructed from conventional building materials and exposed to simulated flooding. Conditions resembling the flooding after Hurricane Katrina in New Orleans, LA, were mimicked, specifically long‐term flooding (3 weeks) and standing periods (3 weeks). The effect of natural drying of the FU, followed by forced drying, on the moisture and mechanical integrity of building elements and components was studied. The results were compared with a similar study where the flood and standing times before drying were considerably shorter (3 and 5 days, respectively). The long‐term flood exposure and delayed re‐entry resulted in severe delamination and blistering of the gypsum board below water level on almost all the walls of the FU. Natural ventilation by opening windows was not effective in reducing the moisture content of the gypsum board. A combination of dehumidification and air conditioning dried the FU and test samples in about 1 week. Short‐term (3 days) flood exposure and re‐entry 5 days later caused significantly less visual damage to the walls of the FU in comparison with the long‐term exposure. Mechanical testing of the interior wall samples yielded similar results for both the long‐term and short‐term studies. For both studies, the mechanical strength above and below the water line was similar after the prescribed drying period. This type of data is important in order to utilise most effectively the components of a structure affected by flooding, as well as for development of protocols for the restoration of building components.